2020
DOI: 10.1111/tpj.14996
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathways regulating elongation of aerial plant organs: a focus on light, the circadian clock, and temperature

Abstract: Summary Organs such as hypocotyls and petioles rapidly elongate in response to shade and temperature cues, contributing to adaptive responses that improve plant fitness. Growth plasticity in these organs is achieved through a complex network of molecular signals. Besides conveying information from the environment, this signaling network also transduces internal signals, such as those associated with the circadian clock. A number of studies performed in Arabidopsis hypocotyls, and to a lesser degree in petioles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 376 publications
0
11
0
Order By: Relevance
“…It is then obvious that phytohormones inevitably interfere with one another, as they target common processes of plant development. DELLA interactions with key regulators of hormone pathways highlight interactions with GA, BR and auxin signalling to regulate cell elongation (Davi ere Franciosini et al 2017;Bour e et al 2019;Favero et al 2021). For instance, DELLA proteins bind to AUXIN RESPONSE FACTOR 6 (ARF6) and BRASSINAZOLE RESISTANT 1 (BZR1) to modulate auxin and BR responses, respectively (Bai et al 2012;Oh et al 2014).…”
Section: Crosstalk With Other Hormonesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is then obvious that phytohormones inevitably interfere with one another, as they target common processes of plant development. DELLA interactions with key regulators of hormone pathways highlight interactions with GA, BR and auxin signalling to regulate cell elongation (Davi ere Franciosini et al 2017;Bour e et al 2019;Favero et al 2021). For instance, DELLA proteins bind to AUXIN RESPONSE FACTOR 6 (ARF6) and BRASSINAZOLE RESISTANT 1 (BZR1) to modulate auxin and BR responses, respectively (Bai et al 2012;Oh et al 2014).…”
Section: Crosstalk With Other Hormonesmentioning
confidence: 99%
“…2019; Favero et al . 2021). For instance, DELLA proteins bind to AUXIN RESPONSE FACTOR 6 (ARF6) and BRASSINAZOLE RESISTANT 1 (BZR1) to modulate auxin and BR responses, respectively (Bai et al .…”
Section: The Ga Signalling Pathways Drive Integrative Growth Adaptationmentioning
confidence: 99%
“…The Phytochrome Interacting Factor (PIF) is a small subset of basic helix-loop-helix TFs that function as a cellular signaling hub, integrating internal and external stimuli to coordinate the regulation of the transcriptional network that drives multiple morphogenic responses (Leivar and Quail, 2011). The PIF4, PIF5, and PIF7 have been shown that act as clock output controlled by circadian clock genes that manipulated plant growth and development (Cheng et al, 2021;Favero et al, 2021). It is reported that PIF7 negatively regulates DREB1 expression under circadian control in Arabidopsis, consequently repressed DREB1 expression may be important for avoiding plant growth retardation under unstressed conditions.…”
Section: Differentially Expressed Transcription Factors Under Drought...mentioning
confidence: 99%
“…In addition, we examined transcript accumulation from genes that have been directly or indirectly associated with promoting or inhibiting hypocotyl elongation (Supplemental File 3), including genes involved in the biosynthesis, catabolism, or signaling of plant hormones implicated in regulating hypocotyl elongation such as GA and brassinosteroids, genes implicated in cell wall remodeling or acidification, and other genes that have been experimentally implicated in regulating hypocotyl elongation (24,36,37). Notably, several genes with known roles in hypocotyl elongation regulation display ABA-dependent regulation in dark-grown hypocotyls (Table 1).…”
Section: The Aba2 Mutant Reveals Aba-dependent Auxin-regulated Gene Transcriptionmentioning
confidence: 99%